PENGARUH RASIO PROFITABILITAS DAN RASIO LIKUIDITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hartanti, Yunita Dwi; Mustari, Mustari (Teknik Industri Unikom, 2024)
The increasing amount of debt experienced by companies in the transportation sector in recent years has attracted researchers' interest to explore the topic of capital structure as the main focus of this research. This study aims to analyze the effect of profitability ratios and liquidity ratios on the composition of the company's capital structure. The profitability variable is represented using the Return on Assets (ROA) metric, while liquidity is represented by the Current Ratio (CR), and the capital structure is measured by the Debt to Asset Ratio (DAR). The approach used in this research is a quantitative method, with data analysis using Multiple Linear Regression techniques performed with the help of SPSS software. The sample selection was carried out using the Purposive Sampling method on transportation companies listed on the Indonesia Stock Exchange (IDX) during the period 2017-2022. The results showed that simultaneously, profitability and liquidity have a significant influence on the company's capital structure. Separately, profitability has a significant positive influence, while liquidity has a significant negative influence on the company's capital structure.